THE OUTCOMES OF ROUND OFF ARTISTIC GYMNASTICS LEARNING SKILL - Dini Rosdiani; Firmansyah dlis; Mulyana Mulyana (Program Pascasarjana Universitas Negeri Jakarta, 2017)
The purpose of this study was to determine differences in learning outcomes artistic gymnastics round off the overall use of teaching methods and teaching methods section to motor ability in STKIP Pasundan Cimahi. The method used is an experimental method to the design by level of 2x2. The population is all students STKIP Pasundan Cimahi level II Prodi. PJKR Academic Year 2015/2016 by the number of 360 people and the sample of 40 people with the sampling technique used purposive sampling. The research instrument used achievement test round off the artistic gymnastics. This research was conducted as many as 12 meetings. The results showed that: (1) There are differences in learning outcomes between the artistic gymnastics round off the overall teaching methods and teaching methods section. (2) There is no interaction between teaching methods and learning outcomes of motor abilities to round off the artistic gymnastics in STKIP Pasundan Cimahi. (3) There are differences in learning outcomes between the artistic gymnastics round off the overall teaching methods and teaching methods to the student section that has a motor of high ability. (4) There is no difference in learning outcomes between the artistic gymnastics round off the overall teaching methods and teaching methods to the student section that has a motor ability is low... Keywords: Teaching Methods, Motor Ability, Round Off